Spinal Cord Diffuse Midline Glioma With Histone H3 K27M Mutation in a Pediatric Patient - Cheng, Ran; Li, Da-Peng; Zhang, Nan; Zhang, Ji-Yin; Zhang, Di; Liu, Ting-Ting; Yang, Jun; Ge, Ming (Frontiers in Surgery, 2021)
Background: Diffuse midline glioma (DMG) with histone H3 K27M mutation is a recently identified entity documented in the 2016 World Health Organization (WHO) Classification of Tumors of the Central Nervous System. Spinal cord DMGs with H3 K27M-mutant are commonly reported in adults. Herein, we reported a pediatric patient with spinal cord H3 K27M-mutant DMG. Case report: A 7-year-old girl with 1-month history of neck pain and 3-week history of progressive weakness in the right hand was presented. Spinal magnetic resonance imaging showed an intramedullary lesion with slight enhancement at the C2-7 levels. With intraoperative neuroelectrophysiological monitoring, the lesion was subtotally resected. Histopathological examination revealed a DMG with histone H3 K27M mutation corresponding to WHO grade IV. Postoperatively, the neck pain was relieved, and the upper-extremity weakness remained unchanged. Oral temozolomide was administrated for seven months, and radiotherapy was performed for 22 courses. After an 18-month follow-up, no tumor recurrence was noted. Conclusion: Spinal cord H3 K27M-mutant DMGs are extremely rare in pediatric patients. Preoperative differential diagnosis is challenging, and surgical resection with postoperative chemoradiotherapy may be an effective treatment.